Alimentación emocional, calidad de dieta y estado nutricional en escolares de la Institución Educativa N° 60133, Cahuide, San Juan Bautista – 2024 - Acho Alzamora, Almendra Antuanné (2025)
The present study aimed to determine the relationship between emotional eating and diet quality with the nutritional status of schoolchildren attending Educational Institution No. 60133 in the Cahuide population center in the district of San Juan Bautista during 2024. The study was quantitative, descriptive, non-experimental, correlational, and cross-sectional. The sample consisted of 145 students of both sexes from first to sixth grade of primary school. The sampling was convenient. Weight, height, and blood hemoglobin were collected, in addition to a diet quality questionnaire and an emotional eating scale. 37.93% had a normal BMI/E, 42.07% were overweight, 17.24% were obese, and fifth and sixth grades had the highest proportions of overweight. 93.10% were normal height, 6.21% were short, and 0.69% were tall. A total of 27.59% had moderate anemia, 12.41% had mild anemia, and 60.00% had normal anemia, with the first three grades having the lowest hemoglobin levels. 36.55% had an unhealthy diet, 47.59% had a moderately healthy diet, and 15.86% had a healthy diet, with the second, fourth, and fifth grades having the highest unhealthy diets. 29.66% had high emotional eating, with the second, third, and sixth grades having the highest proportions. A statistically significant relationship was found between emotional eating and diet quality and nutritional status indicators.